Moagem de alta energia e deformação plástica severa do Mg e do Mg-Fe na síntese de hidretos para armazenagem de hidrogênio - Antiqueira, Flávio José (2017)
Magnesium is a light metal with a relatively low cost. It can form magnesium hydride (MgH2), which is interesting for the safe storage of hydrogen in the solid state, thanks to its high gravimetric capacity of 7.6%. The Mg application is hampered by its high H2 absorption/desorption temperature and slow kinetics. The High energy ball milling (HEBM) has been successful in preparing Mg-based nanocomposites, resulting in rapid kinetics around 300 °C. However, powder contamination, process time and the need for inert atmosphere to its manipulation are limiting the HEBM. In order to improve its performance, Mg, with or without iron addition, was submitted to two main processing routes. First the HEBM was performed as a reference for the milled powder. In another route, bulk Mg was processed as stacked plates, and also, Fe was added in the form of continuous and fragmented wires, or powdered. In this route, Mg was submitted to severe plastic deformation (SPD) at room temperature, starting with the extensive cold rolling (ECR) and followed by the repetitive cold rolling (ARB). The materials were characterized by X-ray diffraction (XRD), optical microscopy (OM), scanning (SEM) and transmission electron microscopy (TEM). The H2 storage properties were evaluated by differential scanning calorimetry (DSC) and the Sievert’s volumetric method. The Mg submitted to HEBM was superior in the activation, kinetics and H2 storage capacity, compared to the ECR+ARB. The Mg with Fe addition, milled for 10 h, showed optimum kinetics and a large reduction on the desorption temperature. However, the Mg processed by ECR+ARB with Fe addition under varied morphologies, yield a high level of accumulated deformations and defects, permanence of the (002) plane texture and submicrometric grain refinement, reflecting in good activation and high H2 storage capacity, which still requires more studies to overcome the better results of the HEBM.